Education Of Small And Medium Enterprise (Sme) Workers On Processed Chips Related To Low Back Pain (Lbp) As An Effort To Prevent - Damas Tsaniyah Min Rohmatillah; Annisa Tri Andriani; Alif Nur Azka; Maghfiri Shania Bidari; Manuel Umbu Madiaha (DokTIn MEDIKA Jurnal Pengabdian Masyarakat, 2025)
Every year around 380,000 workers die due to workplace accidents or occupational diseases (PAK). Factory workers, workers in the culinary sector, and jobs that involve a lot of repetitive movements have a fairly high risk of PAK. Occupational factors are risk factors for Low Back Pain (LBP), namely excessive use of muscles, repetitive movements over long periods of time, movements with force, and static work postures for long durations of time. The aim of this service is to prevent the occurrence of LBP through education regarding LBP among Zaha workers. This paper is a cross-sectional descriptive study among 3 "ZAHA" MSME workers. Socialization about LBP containing definitions, causes, risk factors, therapy and prevention is given to all workers. The activity carried out was to first conduct a pretest on all workers regarding LBP knowledge. Then provide education about LBP to workers using posters. Then a post-test activity was carried out to assess the workers' understanding after the counseling was carried out. The pretest results showed that almost all the questions had wrong answers. After educating workers about definitions, causes, risk factors, therapy and prevention, the posttest results showed that almost all the same questions could be answered correctly. So that workers gain increased knowledge about Low Back Pain (LBP). Education for "ZAHA" home industry workers has an impact on increasing knowledge about the incidence of Low Back Pain caused by work.